Advanced Cantonese ESL Learners' Use of a Monolingual Dictionary for Language Production - Chan, Alice Y.W. (Lexikos, 2012)
This article reports on the results of a research study which investigated the use of monolingual dictionaries by Hong Kong advanced Cantonese ESL learners in the production of target language sentences. Thirty-one English majors participated in a sentence completion task and a sentence construction task with and without the help of a monolingual dictionary. In the sentence completion task, a full Chinese context and a partial English context were given, whereas in the sentence construction task, only a few English prompts were given. Different self-reporting protocols, including introspective questionnaires, retrospective questionnaires and think-aloud recordings, and a post-task focus-group interview were conducted to tap into the participants' thinking processes during dictionary consultation. The results show that a monolingual dictionary is useful in helping learners produce target language sentences, yet learners encounter different kinds of consultation problems, some of which are related to their general use of dictionaries and others to the language in which their thinking processes are engaged. It is suggested that ESL learners use both monolingual and bilingualized dictionaries in their learning and that ESL teachers design dictionary skills training programs which take into account learners' linguistic competence and actual consultation problems.